An advanced pulmonary sarcomatoid carcinoma patient harboring a BRAFV600E mutation responds to dabrafenib and trametinib: a case report and literature review - Fang, Ruoxin; Gong, Jun; Liao, Zhengkai (Frontiers in Oncology, 2023)
Background The pulmonary sarcomatoid carcinoma (PSC) is a rare and aggressive subtype of NSCLC with rapid progression and poor prognosis, and is resistant to conventional chemotherapy. Most PSC cases have potential targetable genomic alterations. Approximately 7% of PSC patients have BRAF mutations, and the efficacy of dabrafenib and trametinib in BRAFV600E mutated PSC is unclear. Case presentation Our report describes a patient with mutated BRAFV600E PSC who underwent surgery and adjuvant chemotherapy early but quickly relapsed. Both chemotherapy and immunotherapy were ineffective for him, combined dabrafenib and trametinib produced a 6-month progression-free survival, and a partial response was observed in the tumor response evaluation. As a result of financial pressure, he stopped taking the targeted drugs, and his disease rapidly progressed. Conclusion Dabrafenib combined with trametinib provides partial remission in patients with advanced PSC with BRAFV600E mutations, and large-scale NGS panels could offer more options for PSC treatment.